A family's treasure - Lim, Audrelia (Nanyang Technological University, 2020)
“A Family’s Treasure” is a 2D short animation that talks about a greedy and materialistic daughter who wants to buy everything she wants for herself but depending on her father for the money. The aim of this film is to communicate a critic on materialism equating to our level of happiness in today’s addictive consumerism society. This report serves to document my thoughts and processes in creating this film from preproduction to production.